2015
DOI: 10.3389/fpls.2015.00514
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency in barley plants: phytosiderophore release, iron translocation, and DNA methylation

Abstract: All living organisms require iron (Fe) to carry out many crucial metabolic pathways. Despite its high concentrations in the geosphere, Fe bio-availability to plant roots can be very scarce. To cope with Fe shortage, plants can activate different strategies. For these reasons, we investigated Fe deficient Hordeum vulgare L. plants by monitoring growth, phytosiderophores (PS) release, iron content, and translocation, and DNA methylation, with respect to Fe sufficient ones. Reductions of plant growth, roots to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 59 publications
(89 reference statements)
2
39
0
Order By: Relevance
“…DNA methylation has recently been studied in Candida albicans; Metschnikowia reukaufii; Cryptococcus laurentii (now Papiliotrema laurentii); and some species within the Kluyveromyces, Candida, Schizosaccharomyces, and Saccharomyces genera [39,40,42,52]. Despite the involvement of DNA methylation in the rapid response to biotic and abiotic stresses has been widely investigated in plants [46,[53][54][55][56][57], none of the above-mentioned studies have taken into consideration the possible involvement of DNA methylation as a possible response induced in yeast species by cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation has recently been studied in Candida albicans; Metschnikowia reukaufii; Cryptococcus laurentii (now Papiliotrema laurentii); and some species within the Kluyveromyces, Candida, Schizosaccharomyces, and Saccharomyces genera [39,40,42,52]. Despite the involvement of DNA methylation in the rapid response to biotic and abiotic stresses has been widely investigated in plants [46,[53][54][55][56][57], none of the above-mentioned studies have taken into consideration the possible involvement of DNA methylation as a possible response induced in yeast species by cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show differential expression of the genes encoding epigenetic regulatory proteins [77][78][79]. Local chromatin changes and DNA methylation in response to abiotic stresses including cold, drought, salinity, or mineral nutrition are being observed which emphasize the significance of epigenetic regulation during environmental stresses [80][81][82][83][84][85]. Dijk et al [86] reported H3 lysine-4 trimethylation (H3K4me3) to be positively-correlated with the transcription level of drought-responsive genes in Arabidopsis under drought stress.…”
Section: Our Understanding Of the Dynamics And Functions Of Epigenetimentioning
confidence: 99%
“…Recent studies show differential expression of the genes encoding epigenetic regulatory proteins [77][78][79]. Local chromatin changes and DNA methylation in response to abiotic stresses including cold, drought, salinity, or mineral nutrition are being observed which emphasize the significance of epigenetic regulation during environmental stresses [80][81][82][83][84][85]. Dijk et al [86] reported H3 lysine-4 trimethylation (H3K4me3) to be positively-correlated with the transcription level of droughtresponsive genes in Arabidopsis under drought stress.…”
Section: Regulation Of Gene Expression and Genome Stabilitymentioning
confidence: 99%